(untitled) (Bangladesh Journal of Medical Education, 2017)
Background: Teachers’ training is a kind of education that helps the teachers to understand the basic theories of teachinglearning for escalating their knowledge, skills and abilities according to the learner’s need. Objectives: The present study was undertaken to identify the students’ perception about the teaching performances of the teachers who had gone through the training on teaching methodology at Centre for Medical Education (CME) in Bangladesh. Methods: This descriptive type of cross sectional study was conducted in thirteen public and private medical colleges of Bangladesh. A structured questionnaire based on 5-point Likert scale was used to collect the students’ perceptions which included 13 separate positive statements regarding classroom performances. Statements having mean score of 4 or more are considered as positive aspect of performance. Statements with mean score 3 or less indicate the problem area of performance. Statement with a mean score in-between 3 and 4 might be emphasized for further improvement. Results: According to students’ aggregated view, 38% of the teaching performances were excellent, 43% were good, 16% were satisfactory and 3% were unsatisfactory. Conclusion: To ensure excellence in all aspects of teaching performances a well-designed, updated and contextual training programme needs to be adopted for further improvement of teaching-learning. Bangladesh Journal of Medical Education Vol.7(1) 2016: 14-19